Marketing Communications in the Logistics System of Information and Innovation Technologies of the Consumer Market - Filipchuk, Natalia; Konovalenko, Anastasiia; Shkvyria, Natalia; Stankova, Antonina; Bolila, Svitlana (My University, 2022)
The article considers marketing communications in the logistics system of information and innovation technologies of the consumer market. The determinant of the development of marketing communications of the enterprises-participants of the consumer market with prospect of introduction of information and innovative technologies, considering conditions of formation of their logistic system for an estimation of qualitative protection of results of financial activity, is defined. Stages of transformation of marketing communications of enterprises are substantiated, depending on the degree of high-tech development of logistics systems in the world and the chosen strategy of promotion of information-innovative technologies, which creates both internal system of Intranet-environment and external system of Extranet-environment. The stages of clustering of enterprises according to the level of the development of marketing communications in the logistics system of information and innovative technologies of the consumer market of the food industry are systematized. A comprehensive assessment of the level of the development of marketing communications of food industry enterprises in logistics systems of information and innovation technologies of the consumer market is made. The world level of the development of marketing communications in the logistics system of information and innovative technologies of the consumer market of the food industry is analyzed. The share of the population of the world by language affiliation of the use of information and innovative technologies of the consumer market of the food industry is determined. Taxonomic indicators of the level of development of marketing communications at the enterprises of the food industry are used.
Keywords: Food industry enterprises; financial activity; information and innovation technologies; investors; logistics system; marketing communications